Epileptic discharges specifically affect intrinsic connectivity networks during absence seizures - Zhang, Z; Liao, W; Wang, Z; Xu, Q; Yang, F; Mantini, D; Jiao, Q; Tian, L; Liu, Y; Lu, G (2014)
Intrinsic connectivity network (ICN) technique provides a feasible way for evaluating cognitive impairments in epilepsy. This EEG-fMRI study aims to comprehensively assess the alterations of ICNs affected by generalized spike-and-wave discharge (GSWD) during absence seizure (AS). Twelve fMRI sessions with GSWD, and individually paired non-GSWD sessions were acquired from 16 patients with AS. Ten ICNs corresponding to seizure origination and cognitive processes were extracted using independent component analysis. Intra- and inter-network connectivity alterations of the ICNs were observed through comparisons between GSWD and non-GSWD sessions. Sequential correlation analysis between GSWD and the ICN time courses addressed the immediate effects of GSWD on ICNs during AS. GSWD-related increase of intra-network connectivity was found only in the thalamus, and extensive decreases were found in the ICNs corresponding to higher-order cognitive processes including the default-mode network, dorsal attention network, central executive network and salience network. The perceptive networks and motor network were less affected by GSWD. Sequential correlation analysis further demonstrated different responses of the ICNs to GSWD. In addition to GSWD-related functional excitation in the thalamus and functional suspension in the default-mode network, this study revealed extensive inhibitions in the other ICNs corresponding to higher-order cognitive processes, and spared perceptive and motor processes in AS. GSWD elevated synchronization of brain network activity and sequentially affected the ICNs. © 2013 Elsevier B.V. All rights reserved.